Model for devising and defining technical development projects of motor transport enterprises - Smyrnov, Yevhenii; Borysiuk, Dmytro; Volobuyeva, Tetyana; Nastenko, Mariia; Plakhtii, Tetyana (Eastern-European Journal of Enterprise Technologies, 2023)
The efficiency of work of a large part of the motor transport enterprises of Ukraine is unsatisfactory. For the most part, this situation is associated with significant wear and tear of the fixed assets of enterprises, both rolling stock and the production and technical base. One of the ways to solve this problem is technical development. Under modern conditions, technical development requires a systemic approach, which involves a comprehensive renewal of rolling stock and the production and technical base, taking into account all the interrelationships between these subsystems. To solve this problem, a model of technical development of motor vehicle enterprises was developed in the work, which allows to identify promising strategies, and for their implementation to form and research technical development projects. To select the optimal technical development project, the objective function is substantiated in the work, which includes a technical indicator – the technical readiness ratio and economic indicators – net present value and the payback period of the project. The selection of the optimal project is proposed to be carried out on the basis of the «worst case method». Using this method, the weighting coefficients of the objective function criteria were determined, which corresponded to: for the coefficient of technical readiness – 0.333, for the net present value – 0.556, for the payback period – 0.111. Based on the developed models and algorithms, strategies were determined and technical development projects of the Vinnytsia branch of the private enterprise «Avtotranskom» were developed. Based on the developed objective function and the «worst case method» the optimal technical development project among the developed ones was determined. Implementation of this project allows to increase the technical level, work efficiency and competitiveness of the enterprise